Critique and Study of the Reasons for the Widely Known Viewpoint on the Ritual Impurity of the Unbelieversâ Underage Children - Ã˜Â§Ã˜ÂÃ™Â…Ã˜Â¯Ã™Â¾Ã™ÂˆÃ˜Â±, Ã˜Â§ÃšÂ©Ã˜Â¨Ã˜Â± (Ã™ÂÃ™Â‚Ã™Â‡ Ã™Âˆ Ã˜Â§Ã˜ÂµÃ™ÂˆÃ™Â„)
One of the issues that has been more or less discussed among jurists and has followed by some discourses has been the innate impurity of the unbelieversâ underage children. The Sunni jurists believe in the cleanliness (á¹ahÄrat) of human beings despite their type of tendencies and beliefs, which naturally includes the unbelieversâ children, too. In contrast, however, most of the ShÄ«âas believe that the unbelieversâ underage children follow their fathers and, like them, are considered as impure. In support to their viewpoints, these jurists have provided reasons that are all of them, as well as their evidences, critically reviewed and their feeble arguments are shown from different aspects and finally the theory of physical purity of the unbelieversâ children, whether in the field of the people of Scripture or the polytheists, is approved and some evidences have also been provided in this respect.